An unusual case report of generalized pulp stones in young permanent dentition - Surendrakumar K Bahetwar; Ramesh Kumar Pandey (Wolters Kluwer Medknow Publications, 2010)
Pulp stones are relatively frequent finding on bitewings and periapical radiograph, but their occurrence in the entire dentition is unusual. Such an unusual occurrence of generalized pulp stone was reported in a 13-year-old girl. The dental, medical and family histories as well as the findings from the clinical examination of the patient were not contributory. Biochemical analysis of the removed pulp calcification from one of the teeth during endodontic treatment showed large amount of calcium, phosphorus, and carbonate. However, metabolic evaluation of patient through liver function test, kidney function test , and blood investigation did not show any metabolic disorders. Patient was also evaluated for any systemic, syndromic or genetic involvement, but this was also non-contributing. Therefore, it is suggested that this unusual cases may be of idiopathic origin.